Effect of low molecular weight natural rubber on mixing and vulcanized properties of low energy processing natural rubber - Saengchao Thongseenuch; Wirach Taweepreda; Krisda Suchiva (Penerbit Universiti Kebangsaan Malaysia, 2017)
Compounding of natural rubber (NR) requires high energy due to the high viscosity characteristic of NR. In order to reduce the viscosity, low molecular weight of NR (LNR) latex was prepared from field latex by using oxidative phenyl hydrazine/O2 system. LNR latex was mixed with high ammonium NR latex at 3, 5 and 10 phr to provide low energy processing NR (LEPNR). Viscosity molecular weights (Mv) of obtained LNR were 42.59, 18.42 and 6.66 kg/mol, respectively. It was found that the maximum Mooney viscosities and ML 1+4@100°C of LEPNRs were significantly decreased with a decrease of Mv of LNR and an increase of LNR content as well. Specific mixing energy consumptions for mastication step and carbon black incorporation step in Brabender Plasticorder were characterized. The results showed that the mixing energy consumption decreased with an increase of LNR content and a decrease of Mv of LNR. Furthermore, an addition of LNR lowered the viscosity of the compounded rubber, slightly shortened the scorch time, and significantly changed the cure time. Although LNR dropped 50% and 100% modulus of vulcanized rubber, it slightly effected the tensile strength of the vulcanized rubber.